Arsenic - Poison or medicine? - Karolina Kulik-Kupka; Aneta Koszowska; Anna Brończyk-Puzoń; Justyna Nowak; Katarzyna Gwizdek; Barbara Zubelewicz-Szkodzińska (Nofer Institute of Occupational Medicine, 2016)
Arsenic (As) is commonly known as a poison. Only a few people know that As has also been widely used in medicine. In the past years As and its compounds were used as a medicine for the treatment of such diseases as diabetes, psoriasis, syphilis, skin ulcers and joint diseases. Nowadays As is also used especially in the treatment of patients with acute promyelocytic leukemia. The International Agency for Research on Cancer (IARC) has recognized arsenic as an element with carcinogenic effect evidenced by epidemiological studies, but as previously mentioned it is also used in the treatment of neoplastic diseases. This underlines the specificity of the arsenic effects. Arsenic occurs widely in the natural environment, for example, it is present in soil and water, which contributes to its migration to food products. Long exposure to this element may lead to liver damages and also to changes in myocardium. Bearing in mind that such serious health problems can occur, monitoring of the As presence in the environmental media plays a very important role. In addition, the occupational risk of As exposure in the workplace should be identified and checked. Also the standards for As presence in food should be established. This paper presents a review of the 2015 publications based on the Medical database like PubMed and Polish Medical Bibliography. It includes the most important information about arsenic in both forms, poison and medicine. Med Pr 2016;67(1):89-96